Radiation Characteristics of a Planar Strip Dipole Antenna and a Slot Dipole Antenna for THz Applications - Apriono, Catur; Rahardjo, Eko Tjipto (Makara Journal of Technology, 2013)
The development of a THz system often requires a device that is used to radiate or detect THz waves. One way to fulfill this requirement is to use an antenna. Therefore, we need to consider the radiation characteristics of an antenna working in the THz region. In this paper, we present simulation study of two dipole antennas, i.e. a planar strip dipole antenna and a slot dipole antenna. The simulation results show that a planar strip dipole antenna has a better radiation efficiency (more than 95%) compared to the slot dipole. It also shows that an efficiency of more than 98% can be achieved when using silicon dielectric substrate. Furthermore, a return loss characteristic of 38,752 dB can be achieved by using a silicon dielectric substrate and a metal layer of Au for the planar slot dipole antenna.